KAJIAN FIKIH JINAYAH SEPUTAR PENANGGULANGAN VIRUS CORONA - Hendra Gunawan (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
The world is now hit by the popular Corona virus pandemic called Covid 19 which has claimed many lives, nearly millions of human lives have been lost due to the ferocity of the Corona virus. Every human being created by Allah SWT has the duty to be khalifatullah fil ardhi (the leader in the universe) must always try to hack the Corona virus that is threatening the universe inhabitants of the universe. Especially Muslims, must contribute in tackling the Corona virus pandemic outbreak, including through jinayah fiqh studies. As for the main problem in this article is how the rules of jinayah in tackling this Corona virus which the author will summarize in the subtitles about a set of jurisprudence rules in dealing with the Corona virus.The method used in this article is descriptive qualitative, through the study of literature in various books and websites that discuss Corona considering that this topic is still new so that not many have studied it in one book.The author's findings in this article, that government policies in tackling the spread of the Corona virus in the country of Pancasila, have synergy with the rules in jurisprudence starting from techniques to isolate victims of the Corona virus to maintaining distance or physical contact in peace. For further details please see the next discussion.